2022
DOI: 10.3390/ijms23042281
|View full text |Cite
|
Sign up to set email alerts
|

HOXB9 Overexpression Promotes Colorectal Cancer Progression and Is Associated with Worse Survival in Liver Resection Patients for Colorectal Liver Metastases

Abstract: As is known, HOXB9 is an important factor affecting disease progression and overall survival (OS) in cancer. However, its role in colorectal cancer (CRC) remains unclear. We aimed to explore the role of HOXB9 in CRC progression and its association with OS in colorectal liver metastases (CRLM). We analysed differential HOXB9 expression in CRC using the Tissue Cancer Genome Atlas database (TCGA). We modulated HOXB9 expression in vitro to assess its impact on cell proliferation and epithelial-mesenchymal transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The aberrant expression of HOXB9 in tumors was not only prognostic predictor but also indicator of response to target therapy. Protein encoded by HOXB9 functioned as oncoprotein and could accelerate cell proliferation and invasion in endometrial cancer, colorectal cancer, and hepatocellular carcinoma cells ( 58 60 ). However, HOXB9 could also delay tumor progression in other kinds of tumors such as gastric cancer and pancreatic cancer ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of HOXB9 in tumors was not only prognostic predictor but also indicator of response to target therapy. Protein encoded by HOXB9 functioned as oncoprotein and could accelerate cell proliferation and invasion in endometrial cancer, colorectal cancer, and hepatocellular carcinoma cells ( 58 60 ). However, HOXB9 could also delay tumor progression in other kinds of tumors such as gastric cancer and pancreatic cancer ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 Despite great advances in the diagnostic and therapeutic strategies, the prognosis still remains dismal because most of the patients develop metachronous or synchronous CRC liver metastases (CRLM). 8 The mechanism of CRC occurrence and metastasis is identified as a multistep and multifactorial process, which may involve various genetic alterations and biological pathways. 9 Studies have found that probiotics can be used as promising ingredients and play vital molecular roles for treating infectious diseases and intestinal-related inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the most common site of CRC metastasis, of which 15%–20% of the patients will be candidates for hepatectomy 7 . Despite great advances in the diagnostic and therapeutic strategies, the prognosis still remains dismal because most of the patients develop metachronous or synchronous CRC liver metastases (CRLM) 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the 39 HOX genes are aberrantly expressed in solid tumors, and their expression is frequently altered in cancer, including lung (Li L. et al, 2019), colon (Bhatlekar et al, 2019;Martinou et al, 2022), breast (de Bessa Garcia et al, 2020), pancreas (Kuo et al, 2019), prostate (Hatanaka et al, 2019), and ovarian cancers (Idaikkadar et al, 2019). Most HOX genes are expressed in the developing vertebrate central nervous system (CNS), where they play essential functions.…”
Section: Introductionmentioning
confidence: 99%